2016
DOI: 10.2495/sdp160601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of location on the physico-chemical properties of water in the Matatiele Local Municipality, South Africa

Abstract: Water security is one of the crucial global issues because of climate change. South Africa is a water scarce country and it is currently facing challenges in water provision, sanitation and supply. The aim of the study was to investigate how location affects the physico-chemical properties of water in the Matatiele Local Municipality. This was achieved by identifying water sources in three categories of location (rural, peri-urban and urban) which are mostly used and measuring their physico-chemical properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…Indeed, drinking water with a pH level above 8.5 indicates that high levels of alkaline minerals are present; high alkalinity does not pose a health risk but can cause esthetic problems such as alkali taste to water (Mulamattathil et al, 2015). As for the electrical conductivity, its higher values leads to high mineral contents such as calcium, chloride, and magnesium in water (Polasi et al, 2016). Determined in drinking water among other things to evaluate the rate of mineralization and the quantity of chemical agents used to treat the water (Kavcar et al, 2009), electrical conductivity has no direct impact on human health (Rahmanian et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, drinking water with a pH level above 8.5 indicates that high levels of alkaline minerals are present; high alkalinity does not pose a health risk but can cause esthetic problems such as alkali taste to water (Mulamattathil et al, 2015). As for the electrical conductivity, its higher values leads to high mineral contents such as calcium, chloride, and magnesium in water (Polasi et al, 2016). Determined in drinking water among other things to evaluate the rate of mineralization and the quantity of chemical agents used to treat the water (Kavcar et al, 2009), electrical conductivity has no direct impact on human health (Rahmanian et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The high turbidity could be ascribed to the absence of filtration for the water samples prior to analysis. Turbidity has no direct impact on health but variable indirect influences through interactions with microbes, heavy metals and other ions [46]. Turbid water has the propensity to serve as vehicles for carrying micro-organisms and shielding them against disinfectants [44].…”
Section: Turbiditymentioning
confidence: 99%
“…Aluminium concentration of more than 200µg/L is not safe for consumption but can be used safely for other domestic activities such as bathing [67]. Erstwhile, groundwater was not a likely source of aluminium, but recent studies have also found high levels of aluminium in groundwater [68,46]. Aluminium toxicity ranges from mild effects like gastrointestinal disturbances to severe forms like hepatic, renal and recently implicated in Alzheimer's disease [69] (Table 3).…”
Section: Aluminiummentioning
confidence: 99%